Improving the Prosperity of Jatirejo Village Community in Pasuruan Regency Through Optimizing the Development of Social Networking MSMEs - Mochamad Mas’ud (LPPM Universitas Yudharta Pasuruan, 2019)
In one of the community service study activities, mentoring students of KKN (Lectures for Real Work) in Jatirejo Village has the potential of marine fisheries in the area of Pasuruan Regency. The condition of the problems faced so far, namely the lack of utilization of marine waste products that have not been managed properly into handicrafts so as to increase the selling value of marine waste that is optimal, lack of knowledge of processing plastic waste products as a craft bag, tissue place, making paving etc., lack of understanding the community to manage the business, both in terms of marketing and finance from the owners of MSMEs in Jatirejo Village, so that the work of the Jatirejo village community is only sold around the Lekok subdistrict. The method of using Participatory Action Research (PAR) is assisting community participation in carrying out activities to improve welfare, especially business management and marketing training, shellfish craft training and the manufacture of plastic packaging water bags, training in the manufacture of plastic paving. The results achieved by the Harmony and RARA Store UMKM online marketing systems have a positive impact, namely an increase in monthly turnover of 33% for each UMKM.